ANALISIS KEPUTUSAN PEMBELIAN PADA PENGGUNA APLIKASI GOJEK FITUR GOFOOD - Dival Larkhin Destamar (2021)
This research is a quantitative research which aims to analyze and determine the effect of promotion, price, and service quality on purchasing decisions. The population used in this study are people who use the GoFood feature of the Gojek application and live in the South Jakarta area. The number of samples to be taken in this study were 75 respondents, for the sampling method in this study using non-probability sampling method and using purposive sampling technique. To collect the research data, will be through distribution using an online questionnaire in the form of google from. In analyzing research data, it was carried out using the inferential analysis method through PLS (Partial Least Square) with the SmartPLS version 3 software. The results obtained from the research that have been done are that (1) promotion has a positive and significant effect on purchasing decisions, (2) price has a positive and significant effect on purchasing decisions, (3) service quality has no and insignificant effect on purchasing decisions.